2012
DOI: 10.1111/j.1439-0388.2012.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial D‐loop analysis reveals low diversity in Mangalica pigs and their relationship to historical specimens

Abstract: The genetic relationship between 195 Mangalica and 79 non-Mangalica pigs was studied using mitochondrial D-loop SNP genotyping. Altogether, 35 polymorphic sites and 27 haplotypes were identified. Of the haplotypes, eight and 16 are Mangalica and non-Mangalica specific, respectively, while three contain both Mangalica and non-Mangalica individuals. Genetic distance values and phylogenetic analysis indicate that Mangalica individuals are very closely related, and five haplotypes represent approximately 92% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Moreover, Figure 1a indicates that neither Spanish Iberian nor Hungarian Mangalica have been crossed with Chinese pigs, as they cluster tightly with European wild boars. Although the absence of any Asian signature had already been conclusively shown in Iberian pigs (Ramírez et al, 2014), the evidence in Mangalica was much more limited (Molnár et al, 2013), but is conclusively shown in these data.…”
Section: Resultsmentioning
confidence: 72%
“…Moreover, Figure 1a indicates that neither Spanish Iberian nor Hungarian Mangalica have been crossed with Chinese pigs, as they cluster tightly with European wild boars. Although the absence of any Asian signature had already been conclusively shown in Iberian pigs (Ramírez et al, 2014), the evidence in Mangalica was much more limited (Molnár et al, 2013), but is conclusively shown in these data.…”
Section: Resultsmentioning
confidence: 72%
“…Moreover, pigs can be used as a model for human diseases, such as arthritis, cardiovascular diseases, diabetes and obesity, because pigs are more similar to humans at physiological and gene level, when compared with rodent animal models [2]. According to different sources, the predicted number of pig breeds and lines range from 350 to 730 [13, 14]. Most of these breeds are local, with only 25 found in multiple regions of a country, and a further 33 spread to more than one country [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the major industrial and the few local breeds, Asian and European wild boars, several Asian pig breeds and several other species of the Sus genus have also been included [9, 2729]. However, other local breeds, of which many are endangered, should also be of great interest for genomic studies because of their importance in biodiversity, conservation, local community and even pork production issues [14, 30]. Mangalica is an example of a local/rare breed with a characteristic curly hair phenotype, which is indigenous to Hungary and was developed in the 19 th century [14].…”
Section: Introductionmentioning
confidence: 99%
“…These sequences are highly similar to other species of Cervidae [2, 12-13, 25-27, 33]. The conserved sequence blocks, and the termination-associated sequences can be used for fine-scale population studies, since they are amongst the most rapidly evolving segments in the animal mtDNA [19,24,28].…”
Section: Mitochondrial Genome Sequence Of Cervus Elaphus Hippelaphusmentioning
confidence: 79%
“…The lack of the ''DHU'' arm in tRNA Ser has been reported in other species of Cervidae [8,21,[25][26][27]35]. The non-coding control region contains conserved sequence blocks, and termination-associated sequences; and can be used for fine-scale population studies, since it is amongst the most rapidly evolving segments in the animal mtDNA [17,19,24,28]. The high-throughput approach for sequencing was useful for obtaining the whole mitochondrial genome of red deer, so this method could be used broadly among animal taxa.…”
Section: Discussionmentioning
confidence: 99%